PENGARUH HOLDING TIME DAN MEDIA PENDINGIN PADA CARBURIZINGMATERIAL SUS 630 TERHADAP NILAI KEKERASAN DAN STRUKUR MIKRO - Fikara, Fittonia Aditya (Universitas Lambung Mangkurat, 2021)
Stainless steel is material that mostly used in chemical industry because of its excellence in corrosion resistance, in addition to corrosion resistance, hardness on the surface of the material it is also be considered, to meet these needs material engineering is carried out, which is surface hardening. Carburizing is one method to harden the surface. This study aims to determine the effect of holding time and cooling (water, air, and oil) on carburizing SUS 630 stainless steel to hardness, microstructure, and diffusion depth. The material used is SUS 630 stainless steel, with carbon content 0.02%. The heating process at temperature 1020°C with holding time 1 hour, 2 hours, 3 hours, 4 hours and 5 hours then cooled to water, oil and air cooling. Test results show; 1) the longer holding time the value of hardnesswill increases. The maximum hardness value is at 5 hours holding time are 76HRN(water), 71.4HRN(air), and 78.2HRN(oil); 2) the occurrence of micro structure transformation due to holding time and cooling. The microstructure formed is structure of ferrite, perlite and martensite; 3) the longer holding time, the diffusion depth will increases. The maximum diffusion depth value is 5 hours holding time are 7.55ɥm(water), 10.42ɥm(air), and 9.98ɥm(oil). Keywords : Carburizing, Diffusion, Holding Time, Hardness, Microstructure.